2017
DOI: 10.3945/an.116.013144
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Methods to Assess Children's Diets in the School Context

Abstract: To evaluate the impact of school-based nutrition interventions, accurate and reliable methods are needed to assess what children eat at school. The primary objective of this study was to systematically review methodological evidence on the relative accuracy and reliability of dietary assessment methods used in the school context. The secondary objective was to assess the frequency of methods and analytical approaches used in studies reporting in-school dietary outcomes. Three health databases were searched for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 102 publications
3
42
1
1
Order By: Relevance
“…One small validation study that compared recall to whole day OWRs among 11-to 15-year-old adolescents in the United States found that recalls overestimated energy intakes by about 10% (Kerr et al, 2015). makes it difficult to surmise how accurately children can report recall overall a 24-h period and make comparisons to the present study (McPherson et al, 2000;Tabacchi et al, 2013;Tugault-Lafleur et al, 2017).…”
Section: Discussionmentioning
confidence: 65%
“…One small validation study that compared recall to whole day OWRs among 11-to 15-year-old adolescents in the United States found that recalls overestimated energy intakes by about 10% (Kerr et al, 2015). makes it difficult to surmise how accurately children can report recall overall a 24-h period and make comparisons to the present study (McPherson et al, 2000;Tabacchi et al, 2013;Tugault-Lafleur et al, 2017).…”
Section: Discussionmentioning
confidence: 65%
“…Another limitation was the use of self-reported data. The accuracy of dietary recall methods among children can vary widely depending on children's age and interview conditions (e.g., the retention period, type of prompting, and use (or not) of parental assistance) (Sharman et al 2016;Tugault-Lafleur et al 2017). Studies conducted among children have also confirmed substantial under-reporting of energy intake (McPherson et al 2000;Burrows et al 2010).…”
Section: Discussionmentioning
confidence: 93%
“…The beverage recall survey used in this study, while modified from a validated survey and pilot tested in this setting, has not been validated. Moreover, self-reported dietary information is less comprehensive as compared to observation or plate waste methods [22]. Additionally, while the San Francisco Bay Area and California as a whole have had wellestablished healthy beverage standards since 2005, findings may not reflect other regions of the country.…”
Section: Limitationsmentioning
confidence: 99%